2021
DOI: 10.3390/diagnostics11020321
|View full text |Cite
|
Sign up to set email alerts
|

The Diagnosis of Cystic Fibrosis in Adult Age. Data from the Italian Registry

Abstract: Cystic Fibrosis (CF) registries are an essential resource of epidemiological and clinical data. Although the median age at diagnosis is usually reported in the first months of life, a minority of individuals is diagnosed during adulthood. The aim of this study was to describe demographic, genetic, and clinical characteristics of this subgroup of the Italian CF population by using data from the Italian CF Registry (ICFR). Patients ≥18 years at diagnosis were selected and clinical data at diagnosis were analyzed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 23 publications
0
8
1
Order By: Relevance
“…In a recent study in Turkey, it was found to be 8.3 years 29 . Children are usually diagnosed with CF in the first months of life with the implementation of CF newborn screening in many countries 30 . In our study, the age at diagnosis of children with PCD was significantly older than children with CF.…”
Section: Discussioncontrasting
confidence: 37%
See 1 more Smart Citation
“…In a recent study in Turkey, it was found to be 8.3 years 29 . Children are usually diagnosed with CF in the first months of life with the implementation of CF newborn screening in many countries 30 . In our study, the age at diagnosis of children with PCD was significantly older than children with CF.…”
Section: Discussioncontrasting
confidence: 37%
“…29 Children are usually diagnosed with CF in the first months of life with the implementation of CF newborn screening in many countries. 30 In our study, the age at diagnosis of children with PCD was significantly older than children with CF. The higher depression, burnout, burden, and negative attitudes of mothers of children with CF than mothers of children with PCD may be related to the younger age of children with CF and their greater need for maternal care for all daily practices.…”
Section: T a B L E 1 Sociodemographic Features And Clinical Character...mentioning
confidence: 47%
“…Data from the Italian CF Registry have been published looking at clinical characteristics of 204 patients diagnosed as adults from 2012 to 2018. 16 They similarly found that patients presented with better nutritional status with only 4.1% of males and 9.4% of females being considered underweight, undoubtedly resulting from a low prevalence of exocrine pancreatic insufficiency of 12.2% in comparison to an estimate of approximately 85% in the overall CF population.…”
Section: Clinical Phenotype Of Individuals With a Late Diagnosis Of C...mentioning
confidence: 92%
“…An Italian study looking at the characteristics of 204 adult-diagnosed patients in the period 2012 to 2018 revealed Phe508del to be the most common genetic variant, but only 3 (1.5%) of the patients were homozygous. 16 In 35% of cases, the genotype combination was CF-causing/CF-causing, but slightly more common was the genotype CF-causing/variant of VCC (36%). In almost 18% of causes, the pathogenicity of the second allele was unknown.…”
Section: Genetics Of Patients With An Adult Diagnosis Of Cystic Fibrosismentioning
confidence: 98%
See 1 more Smart Citation